PENERAPAN METODE PEMBELAJARAN MIND MAPPING DALAM MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN AKIDAH AKHLAK SISWA KELAS IX RMBI MTSN 1 BONE - AP., A. Herpiana; Ani, Qalbi Nur; Hardiansyah, Ahmad; Usman, Farhan; Sarea, Muh. Syahrul (Institut Agama Islam Negeri (IAIN) Bone, 2022)
The aim of this study is to improve student activity and learning outcomes using the Mind Mapping learning method in class XI RMBI MTsN 1 BONE Academic Year 2021/2022. This research is a type of Classroom Action Research (CAR). This research was conducted in October at MTsN 1 BONE. The population of this research was the students of class XI RMBI which consisted of 32 students but who became the research subjects only 16 students because they were still limited by the capacity of the number of students in the class due to the pandemic. Data collection techniques using observation, interviews, and tests. The data were analyzed descriptively quantitatively to determine the improvement of learning outcomes and student learning activities. The results showed that there was an increase in student learning outcomes in the first cycle with an average of 38.75 and an increase in the second cycle with an average of 76.50, so the increase in the average value of student learning outcomes was 37.75 percent. Student activity also increased in cycle I in the form of paying attention and listening to explanations as many as 13 students, asking questions as many as 5 students and reading the material as many as 15 students experienced an increase in cycle II. The increase is quite significant, where in paying attention and listening to explanations as many as 16 students, asking questions as many as 8 students, answering questions as many as 8 students and reading material as many as 16 students.